Konsep Maslahah dan Tinjauan Preferensi Konsumsi Islami pada Bulan Ramadhan di Indonesia - Siti Magfiroh; Saiful Ansori; Umi Khomsiyatun (Jurnal Penelitian Agama, 2022)
Consumption is the main activity in human life. Allah created everything in this universe to be managed which in the end humans also consume it. For this reason, it is important to discuss consumption patterns so that someone is always on the path of Islamic consumption as the example of the Prophet Muhammad SAW. The level of consumption in the month of Ramadan generally increases significantly, so it is necessary to conduct research on consumption patterns that lead to maslahah and Islamic consumption preferences. So, this study aims to find out how the concept of maslahah and Islamic consumption preferences during the month of Ramadan in Indonesia. This research is a library research with a qualitative descriptive approach. The results showed that the recovery in household consumption in the first quarter grew in the range of 4.12% and will continue into the second quarter. Likewise on the side of money circulation, where based on the amount of money in circulation, consumption credit grew by 6% in March 2022. Furthermore, the correlation formed in the relationship between maslahah and preferences is that maslahah has an effect on Islamic consumption preferences. The higher the level of maslahah, the closer the individual will be to falah, for that consumption preferences are expected to reach falah immediately as part of the aspect of maximizing maslahah.